CULTURAL IMPERIALISM AND CAPITALISM MEDIA IN ISLAMIC VALUES DECONSTRUCTION ON RAMADAN SHOW IN TELEVISIONS - Umaimah Wahid; Muhamad Isnaini; Ni Gusti Ayu Ketut Kurniasari (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2015)
Indonesia is the country with the largest number of Muslim occupation in the world today. The largest number of Muslims require various forms of religious education as an attempt to provide insight to the community about the concept and values of Islam. In the process, mass media, which has grown rapidly in Indonesia, especially television come to take a role by providing a variety of spectacle that contains values of Islam. Islamic nuances such as soap operas and television speeches adorn the face of Indonesia. The phenomenon was initially only during the Ramadhan 2010-2012. The focus of this paper is about the deconstruction of Islamic values in TV’s programs, cultural imperialism and mass media capitalism which implies the reconstruction of religious understanding of the ummah. The emergence of commodification and religious shows on television structuration as a form of capitalism media. This means that the value of profit is the primary consideration nuanced spectacle of Islam on television. That led to a new cultural imperialism in the community because dekonstrusi Islamic values by the mass media in beragamma tv program in the month of Ramadan. Comodification and structuration in the mass media thus changing the value of media is becomes a commodity that has economic value All that become on understanding community that increasingly loose with values of Islam. community more enjoy to understanding the religious impressions are nothing more than a mere entertainment. Reality is changing the way of thinking, attitudes and behavior which was originally more confidence to the understanding that comes from the explanation of 'real' in society, switch to the understanding of religion believe that they watch on television.